The Implementation of Mortgage Loan: A Comparative Study between Bank BPD DIY and Bank BPD DIY Syariah - , PINKADELA MASHITTA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mortgage loan (Kredit Pemilikan Rumah/KPR) is a credit facility given by the bank to society. The aim of this loan is to help people fulfilling their primary need, which is housing. This program benefits both parties